Perbandingan Kesenjangan Pendapatan Antar Gender Di Provinsi-Provinsi Yang Ada Di Pulau Jawa - Awaliyah, Lisa Fadilah; Arisetyawan, Kukuh (Universitas Negeri Surabaya, 2023)
This study aims to determine the level of income gap between genders in the provinces on the island of Java and also to determine the factors that affect the income of male and female workers. The data used in this study is the 2020 national labor force data (SAKERNAS). The methods used are robust regression and blinder-oaxaca decomposition. The results of this study found that the factors age, education, employment sector, and technology have a significant positive effect on the income of male and female workers. Meanwhile, the pre-employment card variable has a negative effect on male income but no effect on female income. The marital status variable has a significant positive effect on male income but has no effect on female income. The level of income gap between genders on the island of Java if sorted from the province that has the highest level of income gap is the province of East Java, Central Java, Yogyakarta, West Java, Banten, and DKI Jakarta. The income of female workers has a lower income than the income of male workers. The factor that contributes most to the income gap between genders is the unexplained factor or discrimination rather than the explained factor.